The Effect of Iron (Fe) Tablet Administration on Increasing Hb Levels in Adolescent Girls with Mild Anemia in the Working Area of Ibu Health Center, West Halmahera Regency - Aditia Rusmiati Bessy; Anik Purwati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Adolescence is a period of change or transition from childhood to adulthood, encompassing biological, psychological, and social changes. Adolescent girls experience menstruation every month, which puts them at risk of anemia, compounded by poor dietary habits and the failure to consume iron tablets. Rapid adolescent growth is linked to nutritional fulfillment or adolescent consumption of nutrients, one of which is iron consumption. Insufficient iron consumption can lead to anemia in adolescents. Strategies to address anemia in adolescent girls include improving dietary intake and providing iron tablet supplementation. Changing dietary patterns is an important long-term strategy, but cannot be expected to be successful quickly. Anemia is a global health problem, especially in developing countries, where an estimated 30% of the world's population suffers from anemia. Adolescent girls are ten times more likely to suffer from anemia than boys. Efforts to prevent anemia in adolescents through iron tablet supplementation are a strategic, specific intervention to prepare healthy mothers-to-be. The aim was to determine the effect of iron (Fe) tablet administration on increasing Hb levels in adolescent girls with mild anemia. This study was quantitative, with an experimental design. The population in this study were 55 young women at the Ibu Health Center in West Halmahera Regency. A purposive sample of 30 samples was taken. Data collection in this study was carried out by examining Hb levels before and after administering iron tablets 4 times in a row for 4 weeks. The results of the study were that there was no significant difference between Hb levels before and after administering iron tablets in young women at the Ibu Health Center in West Halmahera Regency. The average Hb level before administering iron tablets was 11.5 g/dL, and after administering iron tablets was 12 g/dL. The results of the paired t-test showed a difference before and after administering iron tablets (p value = 0.001), so the test has an effect on administering iron tablets (Fe) on increasing Hb levels in young women with mild anemia in the Ibu Health Center in West Halmahera Regency.